2011
DOI: 10.1007/s00213-011-2219-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the discriminative stimulus effects of ethanol and its GABAA receptor mediation in cynomolgus monkeys

Abstract: Rationale Excessive alcohol consumption is less common among aged compared to young adults, with aged adults showing greater sensitivity to many behavioral effects of ethanol. Objectives This study compared the discriminative stimulus effects of ethanol in young and middle-aged adult cynomolgus monkeys (Macaca fascicularis) and its γ-amino-butyric acid (GABA)A receptor mediation. Methods Two male and two female monkeys trained to discriminate ethanol (1.0 g/kg, i.g.; 60-min pre-treatment interval) from wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(60 reference statements)
2
12
0
Order By: Relevance
“…Ethanol, for example, has been shown to be complex multielement discriminative stimulus with serotonergic, glutmatergic, dopamingergic, opioid, and GABAergic components (Grant, 1999;Kostowski & Bietikowsi, 1999;Stolerman, Mariathasan, White, & Olufsen, 1999). A future investigation might substitute other GABA agonists (Helms & Grant, 2011), glutamate antagonists (Besheer et al, 2009), serotonin agonists (Grant, Colombo, & Gatto, 1997), or mu opiate agonists (Plat & Bano, 2011) during extinction to determine the relative impact on responding evoked by the original ethanol S^. Additionally, other cholingergic ligands such as varenicline could be substituted during opérant extinction (cf Reichel, Murray, Barr, & Bevins, 2010, for a Pavlovian analog).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol, for example, has been shown to be complex multielement discriminative stimulus with serotonergic, glutmatergic, dopamingergic, opioid, and GABAergic components (Grant, 1999;Kostowski & Bietikowsi, 1999;Stolerman, Mariathasan, White, & Olufsen, 1999). A future investigation might substitute other GABA agonists (Helms & Grant, 2011), glutamate antagonists (Besheer et al, 2009), serotonin agonists (Grant, Colombo, & Gatto, 1997), or mu opiate agonists (Plat & Bano, 2011) during extinction to determine the relative impact on responding evoked by the original ethanol S^. Additionally, other cholingergic ligands such as varenicline could be substituted during opérant extinction (cf Reichel, Murray, Barr, & Bevins, 2010, for a Pavlovian analog).…”
Section: Discussionmentioning
confidence: 99%
“…Nonhuman primate studies have primarily focused on ethanol’s action at the GABA A and NMDA receptors, with some work on the opioid system. Additionally, nonhuman primate work has examined other biological variables that may contribute to ethanol’s discriminative stimulus effects, such as sex [7376], age [77], and menstrual cycle [78]. …”
Section: 1 Rodentsmentioning
confidence: 99%
“…In the luteal phase, when progesterone levels are high, allopregnanolone is more potent in its substitution for ethanol, consistent with greater levels of allopregnanolone in the plasma. Lastly, one study examined the effect of age on ethanol discriminative stimulus effects and determined that ethanol served as a relatively weaker stimulus in middle-aged monkeys, despite elevated blood ethanol concentrations relative to when the same monkeys were young adults [77]. Additionally, this study demonstrated that ethanol discrimination was persistent and demonstrated up to 3 years without any intermediate training [77].…”
Section: 1 Rodentsmentioning
confidence: 99%
“…In a recent study in our laboratory of the effects of aging in cynomolgus macaques that previously acquired ethanol discrimination, a female monkey that had been trained to discriminate 1.0 g/kg ethanol over a decade earlier demonstrated a decrease in the substitution potency of ethanol with age, which further decreased after bilateral ovariectomy (Helms and Grant, 2011). This trend suggests that the absence of ovarian-derived hormones alters the mechanisms mediating the discrimination of ethanol.…”
Section: Introductionmentioning
confidence: 99%